Оцінка відповідності стандартам якості у Європейському Союзі - Кузьмін, О. Є.; Мельник, О. Г.; Юринець, О. В.; Логвиненко, Р. Л.; Kuzmin, O. Ye.; Melnyk, O. H.; Yurynets, O. V.; Lohvynenko, R. L. (Видавництво Львівської політехніки, 2019)
Спрямовано увагу на проблеми забезпечення процедури оцінки відповідності європейським стандартам якості, на котрі активно переходять у зв’язку із гармонізацією вітчизняної системи стандартів. Розглянуто необхідність оцінювання відповідності в іноземному сертифікаційному центрі для отримання подальшої можливості реалізації продукції на ринках збуту ЄС. Досліджено актуальну ситуацію у галузі стандартизації, технічного регулювання та оцінювання відповідності в Україні, котрі перебувають у фазі модернізації та реформування. Виокремлено основні проблеми у цій галузі, характерні для вітчизняних підприємств, шляхом вирішення яких може стати звернення до іноземних сертифікаційних центрів для підтвердження відповідності стандартам.

The article is dedicated to the topical issue of the realization of the European quality standards conformity assessment procedure, which is undergoing an active transition in connection with the harmonization of the domestic system of standards. In particular, the need to pass conformity assessment in a foreign certification center is considered in order to obtain further opportunities for placing products on the EU markets. During the development of the article, the current situation in the field of standardization, technical regulation and conformity assessment in Ukraine, which are in the phase of modernization and reformation, was investigated. In addition, the main problems in this area faced by domestic enterprises were highlighted, the solution of which could be to appeal to foreign certification centers to confirm compliance with the standards. To substantiate the need for the transition to EU quality standards and passage of conformity assessment abroad, the statistical data on the geographical structure of exports of commodity group 8518000000 products was analyzed. As a result, it was determined that more than 75 % of all exports are made to the EU territory. Such results testify to the prospects of the indicated market and the expediency of Ukrainian commodity producers output on it. As far as one of the requirements of market surveillance in the EU is the presence of a certificate of conformity of the product characteristics to the standards, a comprehensive technology for passing the procedure for assessing the conformity of the standard EN 54-24 has been developed on the basis of the Lviv enterprise LLC RPE “Electroprylad”. The implementation of the recommended technology will enable the company to further place its products on the EU market and thereby expand its activities and develop the factory. In addition, the developed mechanism is characterized by the universality of its ability to be used by various domestic enterprises, including for passing the assessment of compliance with other EU quality standards.
Quality standards conformity assessment in the European Union
Keywords: євроінтеграція; зона вільної торгівлі; зовнішньоекономічна діяльність; технічне регулювання; оцінка відповідності; стандартизація; гармонізація стандартів; інтенсифікація експорту; eurointegration; free trade zone; foreign economic activity; technical regulation; conformity assessment; standardization; standards harmonization; export intensification; 339; 005.336.3; 006ЄС